Investing in monarch conservation: understanding private funding dynamics - Solis-Sosa, Rodrigo; Semeniuk, Christina A. D.; Larrivée, Maxim; Cox, Sean (Frontiers in Conservation Science, 2022)
NGOs rely heavily on external donors to fulfill their mandates. However, long-term planning for donations is nothing short of elusive. Since donors’ attention and funding allocations fluctuate over time as conservation scenarios change, NGOs must incorporate this insight into their budgeting plans. We hypothesize that an NGO can hinder its capacity to reach its conservation goals by neglecting its donor-NGO-natural system (DNNS), which is reactive to the socio-ecological context. Using a discrete choice experiment (DCE) and a systems dynamics model, we developed a coupled social-ecological model of the eastern Monarch butterfly (Danaus plexippus), a charismatic long-distance migrant butterfly whose numbers have declined throughout North America. Our study compares the ecological outcomes of assuming donor willingness to pay constant throughout the program (open-loop) to the reality that donor preferences change over time (closed-loop) as ecological context changes, finding significant differences between both approaches. Then, we used two different willingness to pay (WTP) behavioural models, one representing donors informed about the success of the program supported (GPI), and the other without such information (GPI), and demonstrated how changing the underlying assumptions about the target donors can drastically affect fundraising strategies. Next, we also estimated the NGO’s optimal yearly donation requests to achieve a conservation target and found that the conservation objectives and funds raised were consistently and efficiently achieved using our closed-loop model to estimate optimal donation requests. Then, we applied the optimization results from the previous step into a model parameterized with a different behaviour model to test the implications of presuming an incorrect WTP behaviour model, highlighting the importance of acknowledging the dynamic nature of donors’ behaviour and the need to characterize such behaviour thoroughly. Finally, we designed a novel visual tool from the behaviour WTP model exploration to bridge the gap between science insights obtained from DCEs and decision-making. In this paper, we introduced a novel forecasting tool that conservation managers will have at their disposal to improve the accuracy of their budget forecasting and, ultimately, increase the program’s success rate.